2007
DOI: 10.1002/app.25818
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical properties of hydrous electrorheological elastomers based on gelatin/glycerin/water hybrid

Abstract: Aimed at improving the stability of geometrical shape, mechanical performance, and particles dispersion of electrorheological (ER) hydrous elastomers, a new gelatin water-based elastic gels containing starch particles were prepared under an applied dc electric field, and their ER effects were described with the compression modulus and the electric resistivity. The result demonstrates that the mechanical and electrical properties of the ER elastomers are dominated by an externally applied electric field as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…That is because of hydrogen bond between the amino and carboxyl groups which restrains the polarization of active groups. [28] Starch, a natural matter of food and biomaterials, is inexpensive, easily prepared, nontoxic, biocompatible, and degradable in the environment. [30] Additionally, the large numbers of hydroxyl groups on the chains can lead to strong molecular interactions, which is conducive to generate intense electroresponse of the starch hydrogel (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…That is because of hydrogen bond between the amino and carboxyl groups which restrains the polarization of active groups. [28] Starch, a natural matter of food and biomaterials, is inexpensive, easily prepared, nontoxic, biocompatible, and degradable in the environment. [30] Additionally, the large numbers of hydroxyl groups on the chains can lead to strong molecular interactions, which is conducive to generate intense electroresponse of the starch hydrogel (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously prepared gelatin composite hydrogel and studied its favorable electro-responsive properties. [27][28][29] Gelatin, as a biological macromolecule, contains amino and carboxyl groups which are active in forming the network structure of hydrogel. Such active groups in high polymer play very important roles in electrical stimulation response behavior of hydrogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the maximum elastic modulus increment sensitivity (Δ G / G R , where Δ G is the storage modulus increment, G R is the storage modulus of the elastomer cured without electric field) was only 79.32% under the measured electric field of 1 kV/mm. In addition, Gao and Zhao prepared starch/glycerin/gelatin hydrogel hybrid elastomers and found that the Δ G / G R attained a maximum value of 21.04% at a measured electric field of 2 kV/mm. Until now, there have been only a few examples of biomolecular hydrogels as matrixes of ER elastomers, such as gelatin, which are limited in green, environmentally friendly properties and low cost in cost , .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Gao and Zhao prepared starch/glycerin/gelatin hydrogel hybrid elastomers and found that the Δ G / G R attained a maximum value of 21.04% at a measured electric field of 2 kV/mm. Until now, there have been only a few examples of biomolecular hydrogels as matrixes of ER elastomers, such as gelatin, which are limited in green, environmentally friendly properties and low cost in cost , . In these reported works, the main problem with the elastomer has been that the elastic Δ G / G R is too low.…”
Section: Introductionmentioning
confidence: 99%